1997
DOI: 10.1111/j.1365-2249.1997.tb08324.x
|View full text |Cite
|
Sign up to set email alerts
|

Specificities of anti-neutrophil autoantibodies in patients with rheumatoid arthritis (RA)

Abstract: SUMMARYThe objective of this study was to characterize antigens recognized by neutrophil-specific autoantibodies from patients with RA. Sera from 62 RA patients were screened by indirect immunofluorescence (IIF). Positive sera were further tested by ELISAs for antibodies against various granule proteins and by immunoblotting of electrophoretically separated cell, granule or nuclear extracts. Forty-two sera (68%) reacted with ethanol-fixed neutrophils. In the ELISAs 32% of the 28 medium to strongly IIF-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…These include a-enolase, 33 catalase, 34 highmobility-group nonhistone chromosomal proteins, 35 actin, 36 cathepsin G, 37 elastase, 31 lactoferrin, 38 lysozyme, 39 and other unidentified targets. 40 With ANCA in which the specificities are not PR3 or MPO, antibody levels are variable but often low, and there usually is no clear correlation with disease activity or other clinical variables.…”
Section: ' 17mentioning
confidence: 99%
“…These include a-enolase, 33 catalase, 34 highmobility-group nonhistone chromosomal proteins, 35 actin, 36 cathepsin G, 37 elastase, 31 lactoferrin, 38 lysozyme, 39 and other unidentified targets. 40 With ANCA in which the specificities are not PR3 or MPO, antibody levels are variable but often low, and there usually is no clear correlation with disease activity or other clinical variables.…”
Section: ' 17mentioning
confidence: 99%
“…If atypical ANCAis reported to clinicians it is essential to mention in the laboratory report that this does not in itself indicate that a patient has SSVV. Atypical ANCApatterns are very often due to the presence of autoantibodies to multiple neutrophil antigens (24). If strong BPI-ANCAis found in serum it may well indicate vasculitis related to an infectious etiology such as subacute bacterial endocarditis or chronic pseudomonasinfection in cystic fibrosis or bronchiectasia patients (23).…”
Section: If-anca Testingmentioning
confidence: 99%
“…Research conducted by Starkebaum and colleagues at the University of Washington33–36 revealed that ICs, in particular IgG targeting neutrophils, are present in RA synovial fluid (SF) and mediate neutrophil activation. Although the literature contains conflicting data regarding the nature and prevalence of anti-neutrophil-binding IgG in RA depending on the method used for analysis of antigenic targets,33,34,37,38 it is estimated that IgG-containing ICs as well as complement C3 activation fragments can be found in the joints of >90% of RA patients 39,40…”
Section: Neutrophil Cell Death As a Potential Contributor To Citrullimentioning
confidence: 99%